Mediações culturais e a experiência turística no espaço urbano: formalidades do olhar turístico sobre a cidade de Buenos Aires - Gayer, Priscila (My University, 2014)
The first subject introduced is concerned with the Cultural Mediation and its concrete implications in the structuring of meaning process. Throughout the theory s arrangements presented, the cultural mediations are understood as symbolic boundaries which shape people s conceptions and actions. In addition to this perspective, the discussion of tourist experience s characteristics is articulated to develop a theoretical ground in order to raise the main research problem. Thus, the investigation proposal set aims at elucidating the influence s dimension of the Social Representation of Tourist Attraction in the meanings produced by the tourist and by the ones who produce the tourist interpretation about the place to be lived in the tourism context. Regarding these issues, the symbolic background that feeds the conception of tourist attraction was brought to light. The Discourse Analysis was fundamental to achieve this result and, beyond it, the method used permitted another concept to be found out: the urban space attractivity. This last term express the fluid meanings existents in everyday life, the ones which words can not fully reach. Due to the word s insuffiency to symbolize this sort of significance, the image is applied as a proper resource to expose the attractivity of Buenos Aires and, for that matter, the Visual Anthropology is worthy.
Inicialmente, é apresentado um debate sobre as Mediações Culturais e suas implicações nos processos de construção de sentido. Entendido enquanto universos simbólicos que orientam as interpretações e projeções práticas dos sujeitos sobre o mundo que o cerca, o conceito de Mediações Culturais e a reflexão acerca das características da experiência turística vêm a compor os princípios teóricos que permitem pensar: em que medida as representações sociais de atrativo turístico influenciam nos sentidos atribuídos ao local, tanto por aqueles que produzem os produtos turísticos quanto por aqueles que os consomem? Diante dessa problemática, o método da Análise de Discurso é utilizado para desvelar os pilares simbólicos sobre os quais se ergue o conceito de Atrativo Turístico. Nesse processo analítico, a concepção de atratividade do espaço urbano é revelada. Uma concepção que remete a sentidos fluídos, diante dos quais a palavra torna-se insuficiência representativa, solicitando uma narrativa interpretativa alicerçada em outras formas expressivas. Finalizando, assim, com o aporte da antropologia visual e a constituição de uma narrativa imagética sobre a atratividade de Buenos Aires.
Keywords: Turismo; Mediações culturais; Experiência turística; Atrativo turístico; Espaço urbano; Buenos Aires (Argentina); Turismo cultural; Cultural mediation; Social representation; Tourist attraction; Urban space; Buenos Aires (Argentina); Cultural tourism